2018
DOI: 10.3329/imcjms.v12i1.35178
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus and dengue virus coinfection: a case report from Bangladesh

Abstract: A case of concurrent chikungunya virus and dengue virus infection is reported here. The patient presented with fever and generalized body ache. Diagnostic work-up revealed chikungunya-dengue co-infection. Dengue is endemic in Bangladesh while chikungunya is a recently emerging infection. As both the viruses are transmitted by a common vector, Aedes spp., such co-infections are likely to increase in coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…3 Chikungunya-dengue co-infections are also to be remembered and such infections have been reported from Bangladesh. 10,[12][13][14][15] Clinical presentation of our cohort was not far different from two different reports from the same 2017 Dhaka outbreak published in literature. 9,16 Features were comparable with other chikungunya cohorts in literature as well.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…3 Chikungunya-dengue co-infections are also to be remembered and such infections have been reported from Bangladesh. 10,[12][13][14][15] Clinical presentation of our cohort was not far different from two different reports from the same 2017 Dhaka outbreak published in literature. 9,16 Features were comparable with other chikungunya cohorts in literature as well.…”
Section: Discussionmentioning
confidence: 58%
“…Disorders (BIRDEM) General Hospital (14), Gulshan Maa O Shishu Clinic Ltd. (64) and LABAID Gulshan (29)] descriptive study was done including adult patients (>18 years) with confirmed diagnosis of chikungunya [confirmed by reverse transcriptase polymerase chain reaction (RT-PCR) (Qualitative One-Step Real-Time Reverse-Transcriptase PCR technology in the ABI 7500 DX instrument with SDS software) (12) or immunoglobulin M (IgM) against chikungunya (done by immunochromatographic test (ICT) for chikungunya IgM/ IgG by using commercially available kits manufactured by SD BIOSENSOR, Republic of Korea) (95)] from July 1, 2017 to October 31, 2017. Patients were followed-up clinically or over phone, as required; specially for rheumatological symptoms; whether they have entered in to sub-acute or chronic phase.…”
Section: A Multi-center [Bangladesh Institute Of Research and Rehabilmentioning
confidence: 99%
“…Common presentations included fever (93, 86.9%) or recent history of fever (14, 13.1%), joint pain (95, 88.8%), rash (25, 23.4%), pruritus (17, 15.9%), diarrhea and/or vomiting (30, 28%), lymphadenopathy (13, 12.1%), gum swelling and/or oral ulcer (5, 4.1%) and oedema (9, 8.4%). Two patients had chikungunya-dengue co-infections 7,8. Most (93, 86.9%) patients were managed as out-patient basis while 14 (13.1%) patients required hospitalization.…”
mentioning
confidence: 99%